A omni-channel transformation in a Brazilian Retailer: the role of Supply Chain - Simões, Eliane Antonio; Lyra, José Roberto; Okano, Marcelo Tsuguio (Revista de Negócios, 2021)
As a more comprehensive evolution of the concept of customer service channels, the omni-channel was driven by the new information communication technologies that have brought the consumer a new dynamic in the relationship with retailers. This new dynamic imposes on the retailer a series of changes in its internal management processes. The consumer shopping journey can start in the cell phone, go through a physical store for experimentation or withdrawal of the product or service, and end up in a social network from an opinion, good or bad, about the service or product. The technology alone is not enough to ensure that during that journey the consumer has satisfactory experience that can boost new sales. It is up to the retailer to prepare its numerous business processes and also its organization, composed of people with their due roles and responsibilities, for this new dynamic. For its part, this consumer when perceiving this value offer is willing to reward the retailer through engagement with his brand and new purchases. In this context, among the most important processes to be adapted to the omni-channel are those involved with the supply chain. A perfect synchrony of this chain is what guarantees products, services or both at a fair price, in the right place and at the right time. This study seeks to investigate, through a single case study, how the introduction of the omni-channel is being managed by a national retailer that markets durable goods of several segments.